(untitled) (Journal of the College of Basic Education, 2022)
In this research, the optical properties of (ZnO, undoped and manganese-doped (ZnO:Mn) films were prepared and studied by weight (1,3,5,7%) using the chemical vapor deposition technique at normal atmospheric pressure (APCVD) on glass bases heated to (400) The optical properties of the prepared films were studied by UV-VIS spectroscopy, and the results showed an increase in transmittance and a decrease in both the absorbance and reflectivity with the increase in wavelength and the doping percentage, while an increase in the optical energy gap with the increase in the doping percentage. Other optical constants represented by the inertia coefficient, the dielectric constant, the real and imaginary parts, and analyze the results.